Multi-functional logic circuits composed of ultra-thin electrolyte-gated transistors with wafer-scale integration. Issue 22 (25th May 2021) - Yu, Ji-Man; Lee, Chungryeol; Han, Joon-Kyu; Han, Seong-Joo; Lee, Geon-Beom; Im, Sung Gap; Choi, Yang-Kyu
Abstract : Wafer-scale integration of electrolyte gated transistors is demonstrated by using iCVD. A solid-state pEGDMA was used as a gate electrolyte, and it configures multi-functional logic circuits, such as inverter, NAND, and NOR with high performance. Abstract : Electrolyte-gated transistors (EGTs) have been widely studied because of their high carrier density, resulting from the formation of an electric double layer (EDL). However, most of the electrolytes previously used for EGTs have been aqueous solution-type or ionic gel-type. Such deposition methods are limited to wet processes, such as liquid drop, dip-coating, or spin-coating. Even though such fabricated EGTs had advantages for printing on flexible substrates or the use of roll-to-roll manufacturing, those electrolyte materials and deposition methods make it difficult to fabricate a top-gate structured transistor, which is advantageous for logic gates and blocks with individual gate control, and large-scale integration on a wafer. In this work, we demonstrated top-gate EGTs with solid-state polyethylene glycol di-methacrylate (pEGDMA) prepared with initiated chemical vapor deposition (iCVD). The fabricated EGTs exhibited an on/off ratio of more than 10 3 . Multi-functional logic circuits, such as inverter, NAND and NOR were also realized by combining the EGTs and a load resistor. A resistor-loaded inverter was demonstrated with a maximum voltage gain of 2.3 with a low supply voltage of 1 V. In addition, the inverter operated at high frequency up to 1 kHz. Both NAND and NOR gate circuits were also well operated.